Divergent cloacal gland photo-responsiveness in male Japanese quail exposed to short days and associated differences in social interactions and reproduction - Dominchin, Maria Florencia (2017)
Quail under short d (SD) reduce their gonadal development, and consequently their cloacal gland (CG) size, aggressiveness, sexual behaviors, and reproductive performance. However, some quail appear nonresponsive to SD inhibition. When male quail were arbitrarily classified according to their CG involution during maximum photoinhibition (5 wk after SD exposure) as either nonresponsive (NR-SD) or responsive (R-SD), NR-SD quail showed intermediate CG volume between R-SD quail and the control quail kept on long d (C-LD). Herein, we evaluate whether NR-SD and R-SD male Japanese quail differ in their social interactions and reproductive performance while under SD; C-LD males were used as fully reproductive control. First, we assessed over 4 consecutive d, brief (5-min) home cage encounters between individually housed CLD, NR-SD, or R-SD males and an unfamiliar C-LD male visitor. To determine male reproductive capacity, the following wk, males received the visit (10-min) of a mature female over 3 consecutive days. C-LD, NRSD, and R-SD resident males showed higher aggressiveness than their photostimulated male visitors, respectively, in 100, 64, and 0% of the studied cases and were also able to, respectively, fertilize 100, 100, and 15% of their female visitors. Second, male-female encounters were again repeated 4 wk later to further assess reproductive performance and behavior. Naive C-LD, NR-SD, and R-SD males also were evaluated to assess potential consequences of the previous male-male interactions on the later performance. The number of males performing aggressive pecks towards females showed a C-LD>NR-SD>R-SD pattern. While mounts, CG contacts, and reproductive capacity showed a C-LD = NRSD>R-SD pattern, copulatory efficiency exhibited an NR-SD>C-LD = R-SD pattern. Sexual behaviors were not modulated by previous male-male brief social interactions. Findings suggest that NR-SD males are able to breed similarly to their C-LD counterparts, which could be considered an indicator of a reduced reproductive dependence on seasonal photoperiod cues. Differences in the expression of aggressions between NRSD and C-LD males may underlie the observed NR-SD improved copulatory efficiency when interacting with females.